Exploring the transitivity system realization in Batak Toba song lyrics discourse: Systemic functional linguistic study - Siahaan, Hiace Vega Fernando; Tarigan, Jenheri Rejeki; Purba, Desmalia; Hutarabat, Ismarini (JOALL (Journal of Applied Linguistics and Literature), 2024)
Transitivity is pivotal in comprehending the precise meaning of song lyrics to effectively convey the messages communicated through the language used in songs. However, transitivity analysis in lyric songs has received substantial attention from academics worldwide, there remains a notable dearth of studies focused on Batak Toba song lyrics, particularly those addressed to children. This research sought to look into how efficient transitivity usage can improve the overall meaning and guidance in song lyrics. It also investigated the relationship between language and culture in Batak Toba song lyrics and how this relationship is reflected in the daily lives of the Batak Toba community Using interactive data analysis and descriptive qualitative methods influenced by Miles, Huberman, and Saldana (2014), this study systematically examined twenty examples of song lyrics to determine the prevalence and variability of transitivity, as well as the relationship between language and culture. The data were analyzed using transitivity as a component of ideational function in Halliday's (2014)’s meta function model. The results showed that songwriters used a range of transitivity elements to convey their ideas. The most frequently used of types of process was the material process, which accounted for 47,8% of all uses. The actor participant, was the most frequently used, accounting for 47,4% of all uses, while the circumstance of location was the most prevalent accounting for 37%. This study highlighted the significance of transitivity analysis in song lyrics and provided valuable insights for songwriters and children. It is essential to comprehend how language and culture interact when communicating ideas through song lyrics. In this context , the message delivered through language in song lyrics is influenced by culture. Therefore, songwriters must consider cultural elements when arranging each word in song lyrics to ensure that the intended message is understood and attracts the audience’s interest. Further researches are required to examine the importance of the transitivity system in song lyrics across various cultures to provide diverse perspective on song lyrics.